Heidegger in ruins between philosophy and ideology - Wolin, Richard (Yale University Press, 2022)
"Martin Heidegger's sympathies for the conservative revolution and National Socialism have long been well known. As the rector of the University of Freiburg in the early 1930s, he worked hard to reshape the university in accordance with National Socialist policies. He also engaged in an all-out struggle to become the movement's philosophical preceptor, "to lead the leader." Yet for years, Heidegger's defenders have tried to separate his political beliefs from his philosophical doctrines. They argued, in effect, that he was good at philosophy but bad at politics. But with the 2014 publication of Heidegger's Black Notebooks, it has become clear that he embraced a far more radical vision of the conservative revolution than previously suspected. His dissatisfaction with National Socialism, it turns out, was mainly that it did not go far enough. The notebooks show that far from being separated from Nazism, Heidegger's philosophy was suffused with it. In this book Richard Wolin explores what the notebooks mean for our understanding of arguably the most important philosopher of the twentieth century, and of his ideas--and why his legacy remains radically compromised."--Dust jacket